2012
DOI: 10.4081/ejh.2012.e10
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of calcitonin gene-related peptide-like cells changes in the lungs of two-kidney, one-clip rats

Abstract: Taking into consideration renal hypertension-induced homeostatic disorders and the key role of calcitonin gene-related peptide (CGRP) in many, systemic functions regulating systems, a question arises as to what an extent arterial hypertension affects the morphology and dynamics of pulmonary CGRP-immunopositive cell changes. The aim of the present study was to examine the distribution, morphology and dynamics of changes of CGRP-containing cells in the lungs of rats in the two-kidney, one-clip (2K1C) renovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…6 Besides the abovementioned studies, no information has been found on the subject of dynamics of changes in CART-IR cells in the urinary tract of hypertensive animals in relation to the duration of the illness. The connection between the duration of hypertension and the number of DNES cells has been documented only in studies of Kasacka and Arciszewska 3 who analyzed the dynamics of changes in the number of NE cells under the influence of 3-, 14-, 28-, 42-, and 91-day hypertension. The aim of their studies was to examine the distribution, morphology and dynamics of changes of calcitonin gene related peptide-containing cells in the lungs of rats in the two-kidney, one-clip (2K1C) renovascular hypertension model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Besides the abovementioned studies, no information has been found on the subject of dynamics of changes in CART-IR cells in the urinary tract of hypertensive animals in relation to the duration of the illness. The connection between the duration of hypertension and the number of DNES cells has been documented only in studies of Kasacka and Arciszewska 3 who analyzed the dynamics of changes in the number of NE cells under the influence of 3-, 14-, 28-, 42-, and 91-day hypertension. The aim of their studies was to examine the distribution, morphology and dynamics of changes of calcitonin gene related peptide-containing cells in the lungs of rats in the two-kidney, one-clip (2K1C) renovascular hypertension model.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the results, the greatest intensity of NE cells in the lungs of rats was noticed 14 days after the surgical procedure. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hypertension) cause disorders of enteroendocrine cell function, reflected in changes in the number, morphology, location, and activity of these cells in the gastrointestinal tract. This illustrates the important role played by these cells in maintaining whole body homeostasis [45,46,47].…”
Section: Systemic and Local Disor-ders And Neuroendocrine Cells Of Thmentioning
confidence: 91%
“…The distribution of CGRP-IR endocrine cells was previously investigated in stomachs of rats (Kasacka 2009) and porcupines (Yaman et al 2007). However, there are no reports in the literature that describe CGRP-IR cells in the intestines of rodents with immunohistochemistry.…”
Section: Duodenummentioning
confidence: 99%